Establishment and improvement of mechanisms of innovative development of public administration in Ukraine - Sychenko, Viktor; Martynenko, Olga; Yakimenko, Sergyi (Public Administration and Regional Development, 2020)
Theoretical approaches and practical experience of formation the mechanisms of innovative development of public administration in Ukraine are investigated. The approach to the formation the mechanisms of innovative development of public administration in the country is substantiated. The classification of real projects of state-administrative innovations is specified. The fact that the defining feature of public administration today is innovative development is beyond doubt for any researcher. Different researchers emphasize different aspects of this process. In some cases, changes are identified with the "stage of transition to a new model of innovative public administration system" and the main problem is the optimal synchronization of changes affecting all aspects of management and essentially lead to the formation of a new public administration system. In other cases, the practical dimension of managerial innovations is emphasized, in connection with which it is stated that "the actual direction of improving public administration is the introduction into its practice of modern methods and technologies of innovation. However, in any case, these are large-scale transformations that are system-creating in nature and lead to institutional changes adequate to the new requirements of innovative development of the country. We agree with researchers who believe that the goal of innovative restructuring of the system of government is not just industry efficiency, optimization of management decision-making and implementation, but "implementation of the main functions of innovative public administration", which primarily include strategic planning and forecasting; integration and coordination of actions of all subjects interested in innovations; initiating and supporting innovation activities; monitoring and control over the implementation of state innovation programs and projects. Thus, management practice shows that new technologies and innovative activities of management entities alone do not ensure the success of administrative reform. It is important to form an innovation infrastructure, which can be considered as an integrating mechanism that unites the activities of public authorities and innovative technologies. The innovative potential of the public administration system is realized through the innovation infrastructure. The latter consists of a set of specialized institutions, centers, organizations that, on the one hand, ensure the implementation of innovation projects and in general the environment of innovation (eg, consulting services or retraining centers), and on the other hand - initiate and create organizational forms for implementation of innovative projects (for example, technology transfer centers or organization of technology parks).